Do armário ao altar: a constituição do sujeito homoafetivo nos jogos de verdade do discurso midiático - Silva, José Josemir Domingos da (2014)
This thesis investigates the discursivization of the homosexual subject in the media. What brought us to this theme was the fact that, nowadays, the relationships between persons of same sex are problematized in media discourse from a connection with the Civil Rights. Considering this, we believe that emergence of new socio-historical practices have transformed the discursive production of the homosexual subject. We consider, from this fact, it is possible to collate, historically, different enunciative places to homosexual subject in the wordings of the media: the ideological/militant gives rise to the right\citizenship discourse. Given this new enunciative position of the subject, we aim to analyze, from the media statements, the discourse about homosexual subject, considering the actual truth games involving marriage and sexual pronouncement. Theoretically, we anchor this research in fundamentals of Discourse Analysis, especially in the dialogue among the ideas of Michel Foucault (2002, 2007a, 2008a, 2008b) with the work of Michel Pêcheux (1995, 2007, 2008, 2009), and the contributions of Jean-Jacques Courtine (2009, 2011) about the Historical Semiology. As methodological act to achieve this study, we identified two thematic pathways - "coming out" and "gay marriage" - inside the archive of discourses through which the homosexual subject is constituted historically. Guiding us through this discursive cropping, we defined three enunciative series based on the covers of magazines Superinteressante (2004), Veja (2003) and Time (2013). The statements of these covers delineate a system of correlation with other publications that compose the corpus: Istoé, Época, The New Yorker, The Village Voice, Newsweek, Le Nouvel Observateur, Elle, Les Inrockuptibles, Valeurs Actuelles and Liberation. In the analysis of this linguisticimagistic materiality, we verified the production of meaning building effects of truth on the homosexual subject, thus, making it the discursive object. Moreover, the discourse by egalitarian marriage constitutes a resistance that produces a new discursivity on the homosexual subject through the Right.